Fabrication of the absorption air-conditioning system / Khairulnizam Bahrim and Suhidi Al-Zahar Ibrahim - Bahrim, Khairulnizam; Ibrahim, Suhidi Al-Zahar (1999)
Air-conditioning system is based on the principle of body comfort. This principle has to be considered as the factors that affect body comfort. The operation of the cycle is due to the principle of the absorption heat from ambience and suits the temperature of the body comfort requirement. The refrigeration is used as a module of absorbing the heat. A conventional air condition usually consists of form basic equipment i.e. evaporator, condenser, compressor or generator and expansion valve. The compressor is used in vapor-compression system whilst the generator which is includes an absorber is used in absorption air-conditioning system. For this project, Lithium bromide / water is used as working fluid based on the characteristic and advantages of the fluid itself. In chapter 3.0, factors for consideration of choosing the working fluid been explained. Absorption air-conditioning system is used the principle of absorbing the lowpressure vapor into approximate absorbing liquid. Embodied in the absorption process is the conversion of vapor into liquid. All this is explain in chapter 4.0, which discuss the theoretical aspect of the absorption system.